Survey article : Islamic political economy - Choudhury, Masudul Alam (Universiti Utara Malaysia, 2001)
The budding field of Islamic political economy as premised on the epistemological roots of Divine Oneness as explained by the Qur'an and the Sunnah (guidance of the Prophet Muhammad) is explained. Several mainstream economic ideas are thus critically examined and their alternative treatment under Islamic political economy is expounded .The process-oriented model termed in this paper as the Shuratic process or the interactive, integrative and evolutionary process (IIE-process) is shown to be central to the methodology of the circular causation and continuity model of unified reality in Islamic political economy.